A liquid supplement capsule, methods of making and using the same, composite separator, battery, and device

CN122950759APending Publication Date: 2026-10-20BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610856714.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-12
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

尤其在电池使用寿命的中后期,电池内部存在电解液耗尽的情况,加速了电池容量衰减

Benefits of technology

[0026]借助上述技术方案,本申请提供一种补液囊、其制备及使用方法、复合隔膜、电池及设备。补液囊包括由无机脆性材料构成的囊壳,囊壳内具有容纳腔,容纳腔内封装有液态物质,液态物质包含与电解液相同或部分相同的组分,囊壳在囊壳外面的压力大于目标压力阈值的情况下破裂以便容纳腔内的液态物质流出囊壳。本申请设置的补液囊,囊壳为无机脆性材料,囊壳能够在电池内部局部压力达到目标压力阈值时囊壳破裂,精准释放与电解液相同或部分相同的液态物质,实现对缺液区域的补给,延缓电池容量衰减、延长循环寿命,提升电池在生命周期中后期的性能表现。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This disclosure discloses a liquid replenishment bladder, its preparation and usage methods, a composite separator, a battery, and a device, relating to the field of battery technology. The liquid replenishment bladder includes a shell made of an inorganic brittle material, with a cavity inside the shell containing a liquid substance. The liquid substance contains components that are the same as or partially the same as the electrolyte. The shell ruptures when the pressure outside the shell exceeds a target pressure threshold, allowing the liquid substance inside the cavity to flow out. The liquid replenishment bladder of this application, with its inorganic brittle material shell, ruptures when the local pressure inside the battery reaches a target pressure threshold, precisely releasing the liquid substance that is the same as or partially the same as the electrolyte. This replenishes the electrolyte-deficient area, delays battery capacity decay, extends cycle life, and improves battery performance in the later stages of its lifespan.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a liquid replenishment bag, its preparation and use method, a composite separator, a battery and a device. Background Technology

[0002] With the increasing demand for high-energy-density, long-life batteries in electric vehicles and energy storage systems, the performance degradation of batteries during deep cycling has become a key bottleneck restricting their application. Especially in the middle and later stages of battery life, electrolyte depletion occurs inside the battery, accelerating battery capacity decay.

[0003] Currently, the solution in related technologies that simply increases the initial electrolyte injection volume is straightforward, but excessive electrolyte can exacerbate side reactions at the electrode / electrolyte interface in the early stages of battery cycling. This can lead to excessive growth of the solid electrolyte interphase (SEI) and increased gas production, which may actually accelerate the initial battery degradation. Summary of the Invention

[0004] In view of this, this application provides a electrolyte replenishment bag, its preparation and use method, a composite separator, a battery, and a device. Its main purpose is to replenish electrolyte in areas of the battery where the pressure reaches a target pressure threshold during battery cycling, thereby mitigating performance degradation caused by uneven electrolyte distribution and depletion.

[0005] Therefore, one object of this application is to provide a fluid replenishment capsule, comprising a capsule shell made of an inorganic brittle material, the capsule shell having a receiving cavity, the receiving cavity being encapsulated with a liquid substance containing the same or partially the same components as the electrolyte, the capsule shell rupturing when the pressure outside the capsule shell exceeds a target pressure threshold so that the liquid substance in the receiving cavity flows out of the capsule shell.

[0006] Optionally, the target pressure threshold is 2.0 MPa to 4.0 MPa.

[0007] Optionally, the size of the capsule shell is 8 μm to 25 μm.

[0008] Optionally, the thickness of the capsule shell is from 150 nm to 800 nm.

[0009] Optionally, the target pressure threshold is determined by the thickness of the shell, the radius of the shell, and the Young's modulus of the inorganic brittle material. The target pressure threshold is proportional to the square of the ratio of the thickness to the radius.

[0010] Optionally, the fluid replenishment bladder is located in the area surrounding the terminal post of the battery cell.

[0011] Optionally, the inorganic brittle material is nano-silica and / or nano-alumina.

[0012] Optionally, the cavity may also contain an additive.

[0013] Optionally, the additive is one or more of fluoroethylene carbonate, vinylene carbonate, and lithium difluorooxalate borate.

[0014] The second objective of this application is to provide a method for preparing a liquid replenishment capsule, which includes the following steps: dissolving a precursor used to form an inorganic brittle material in an organic solvent to form a precursor solution; using a liquid substance as the core phase and based on the precursor solution, using a high-shear emulsification process to prepare a stable oil-in-liquid emulsion, wherein the liquid substance contains the same or partially the same components as the electrolyte; and sequentially subjecting the oil-in-liquid emulsion to interfacial gel encapsulation treatment and temperature sintering treatment to prepare the liquid replenishment capsule.

[0015] Optionally, the precursor is an aluminum alkoxide and / or a silicate; and / or, the aluminum alkoxide is aluminum isopropoxide; and / or, the silicate is tetraethyl orthosilicate.

[0016] Optionally, the preparation method of the fluid replenishment bag further includes: controlling the particle size of the fluid replenishment bag by controlling the rotation speed and duration of the high-shear emulsification treatment; wherein the rotation speed is 3000~10000 rpm and / or the duration is 3~20 min.

[0017] Optionally, the method for preparing the fluid resuscitation bag further includes controlling the thickness of the bag shell by adjusting at least one of the following parameters:

[0018] The concentration of the precursor in the precursor solution is 0.05 ~ 0.8 mol / L when tetraethyl orthosilicate is used as the precursor, and 0.3 ~ 1.5 mol / L when aluminum isopropoxide is used as the precursor. The volume ratio of the core phase to the precursor solution is 1:3 to 1:10. Rotation speed and / or duration of high-shear emulsification treatment.

[0019] The third objective of this application is to provide a composite diaphragm, comprising a diaphragm and an additional layer disposed on the diaphragm, the additional layer comprising the aforementioned fluid replenishment bladder.

[0020] Optionally, the additional layer also includes an adhesive layer, with the fluid filling bladder located within the adhesive layer.

[0021] Optionally, an additional layer is coated onto the diaphragm.

[0022] Optionally, the mass ratio of the fluid filling bladder to the adhesive is 20:80-30:70.

[0023] The fourth objective of this application is to provide a battery comprising the liquid replenishment bladder described in the first aspect above, or the composite separator described in the third aspect above.

[0024] The fifth objective of this application is to provide a battery replenishment method for the battery described in the fourth aspect above, comprising: when the pressure outside the shell of the replenishment bladder in the battery is greater than a target pressure threshold, the shell ruptures and releases at least one of the electrolyte and additives encapsulated in the containment cavity inside the shell, thereby replenishing the target area in the battery where the replenishment bladder is located.

[0025] The sixth objective of this application is to provide a device comprising the fluid replenishment bladder described in the first aspect above, or the composite diaphragm described in the third aspect above, or the battery described in the fourth aspect above.

[0026] Using the above technical solutions, this application provides a liquid replenishment bladder, its preparation and usage method, a composite separator, a battery, and a device. The liquid replenishment bladder includes a shell made of an inorganic brittle material, with a cavity inside the shell containing a liquid substance. The liquid substance contains components that are the same as or partially the same as the electrolyte. The shell ruptures when the pressure outside the shell exceeds a target pressure threshold, allowing the liquid substance inside the cavity to flow out. The liquid replenishment bladder of this application, with its shell made of an inorganic brittle material, ruptures when the local pressure inside the battery reaches a target pressure threshold, precisely releasing a liquid substance that is the same as or partially the same as the electrolyte. This replenishes the electrolyte-deficient area, delays battery capacity decay, extends cycle life, and improves battery performance in the later stages of its lifespan.

[0027] It should be understood that the description in this section is not intended to identify key or essential features of the embodiments of this application, nor is it intended to limit the scope of this application. Other features of this application will become readily apparent from the following description. Attached Figure Description

[0028] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the following description of the embodiments taken in conjunction with the accompanying drawings, wherein: Figure 1 This is a schematic diagram of the structure of a fluid replenishment bladder shown in one embodiment of this application.

[0029] Figure 2 This is an exemplary schematic diagram illustrating a method for preparing a rehydration bag according to an embodiment of this application, used to prepare the rehydration bag described above.

[0030] Figure 3 This is a schematic cross-sectional view of a composite diaphragm as shown in one embodiment of this application. Detailed Implementation

[0031] The embodiments of this application are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and intended to explain this application, and should not be construed as limiting this application.

[0032] The following description, with reference to the accompanying drawings, describes the fluid replenishment bladder, its preparation and use, composite diaphragm, battery, and device proposed in this application.

[0033] Figure 1 This is a schematic diagram of the structure of a fluid replenishment bag provided in an embodiment of this application.

[0034] like Figure 1 As shown, the fluid replenishment bag includes: a shell made of inorganic brittle material, a cavity inside the shell containing a liquid substance, the liquid substance containing the same or partially the same components as the electrolyte, and the shell rupturing when the pressure outside the shell exceeds a target pressure threshold so that the liquid substance inside the cavity flows out of the shell.

[0035] Optionally, liquid substance refers to electrolyte.

[0036] Optionally, liquid material refers to the optimized electrolyte.

[0037] The pressure on the outside of the capsule can be local mechanical pressure or local airflow pressure, which is not limited in this application.

[0038] Optionally, the target pressure threshold is set in response to the local pressure inside the battery caused by SEI thickening and / or internal gas generation.

[0039] In this application, the electrolyte reservoir has a target pressure threshold. When the pressure on the outside of the reservoir (e.g., the local pressure generated during battery use due to SEI thickening, gas production, etc.) exceeds this target pressure threshold, the reservoir undergoes irreversible brittle fracture, thereby opening a release channel. This allows the liquid substance inside the reservoir to flow out of the reservoir and wet the surrounding areas lacking electrolyte. In this way, the electrolyte replenishment reservoir can automatically and precisely replenish electrolyte in the later stages of battery life, under conditions of increased local pressure, mitigating capacity decay caused by electrolyte depletion.

[0040] Among them, the shell made of inorganic brittle materials has stable mechanical properties, and its target pressure threshold can be controlled by process parameters. It has good repeatability and reproducibility. Therefore, the shell made of inorganic brittle materials has the characteristic of high-precision triggering.

[0041] Among them, the shell made of inorganic brittle material has extremely low permeability to organic electrolytes, and can stably store the liquid substances encapsulated in its containment cavity for a long time.

[0042] Among them, the shell made of inorganic brittle materials has excellent high temperature resistance and can adapt to the high temperature environment of batteries.

[0043] Among them, the shell made of inorganic brittle material has the inherent brittle fracture characteristics and no plastic deformation zone, which can ensure that the pressure triggering behavior exhibits a clear "switching" characteristic and avoid gradual leakage.

[0044] Optionally, the inorganic brittle material is nano-silica (SiO2), which is a dense ceramic layer formed by the sol-gel method to form a cavity to encapsulate the liquid substance.

[0045] Optionally, the inorganic brittle material is nano-alumina (Al2O3), which is a dense ceramic layer formed by the sol-gel method to form a cavity to encapsulate the liquid substance.

[0046] Optionally, the inorganic brittle material is a composite material formed from nano-silica and nano-alumina, which is a dense ceramic layer formed by a sol-gel method to form a cavity to encapsulate the liquid substance.

[0047] Al2O3 and SiO2 both have high hardness, high modulus and excellent chemical stability. They do not undergo redox reactions under the conventional lithium-ion battery operating voltage and electrolyte environment, and do not introduce additional side reactions.

[0048] The inorganic brittle material shell of this application has high strength, good sealing performance, and precise triggering pressure, which can effectively avoid accidental rupture in the early stage of cycling. Brittle fracture only occurs when the pressure outside the shell exceeds the target pressure threshold, thus achieving fixed-point and timed replenishment of electrolyte and additives.

[0049] Optionally, the target pressure threshold can be set to 2.0 MPa to 4.0 MPa. If the target pressure threshold of the electrolyte replenishment bladder shell is too low, such as below 2.0 MPa, it may rupture prematurely due to slight compression during battery manufacturing, electrolyte filling, or early cycling stages, leading to electrolyte leakage and exacerbated side reactions. If the target pressure threshold is too high, such as exceeding 4.0 MPa, it is difficult to be triggered by the actual stress generated inside the battery, making effective replenishment impossible. Therefore, controlling the target pressure threshold within the range of 2.0 MPa to 4.0 MPa ensures that the electrolyte replenishment bladder ruptures when the pressure outside the shell exceeds the target pressure threshold during the later stages of battery cycling, i.e., when the risk of electrolyte shortage is highest, allowing the liquid material inside the cavity to flow out of the shell. This achieves efficient and on-demand electrolyte replenishment, mitigates performance degradation caused by interface drying, and extends battery life.

[0050] Optionally, the particle size of the capsule can be set from 8 μm to 25 μm.

[0051] Optionally, the thickness of the capsule shell is from 150 nm to 800 nm. Preferably, the capsule shell thickness is uniform.

[0052] Optionally, considering that film-forming additives (such as fluoroethylene carbonate (FEC), vinylene carbonate (VC), lithium difluorooxalate borate (LiDFOB), etc.) will be irreversibly consumed as battery usage time increases, leading to damage to the electrode interface (especially the negative electrode SEI film) and exacerbation of side reactions, the electrolyte replenishment bladder of this application also encapsulates additives within its containment cavity to repair the electrode interface and delay battery degradation. Optionally, the additives are one or more of fluoroethylene carbonate, vinylene carbonate, and lithium difluorooxalate borate. When the bladder shell ruptures under pressure, the electrolyte and additives are released together into the deficient area, thereby simultaneously replenishing the total electrolyte volume and repairing the electrode interface.

[0053] In this application, considering the mechanical model of a thin-walled spherical shell, the target pressure threshold (Pc) approximately satisfies: Pc = K × E × (h / R)² Where K is a fixed coefficient; E is the Young's modulus of the inorganic brittle material; h is the shell thickness; and R is the shell radius (i.e., half the shell particle size). In other words, the target pressure threshold is determined by the shell thickness, shell radius, and Young's modulus of the inorganic brittle material, and the target pressure threshold is proportional to the square of the ratio of the shell thickness to the shell radius.

[0054] Considering that the fixed coefficient K is generally between 1.18 and 1.2 for nano-silica or nano-alumina, various examples will be given below using Pc = K × E × (h / R)².

[0055] In some implementations, nano-alumina is used as an inorganic brittle material, the average particle size of the fluid replenishment bladder is 8 μm, the thickness of the bladder shell is 150 nm, the Young's modulus of the bladder shell is adjusted to about 1.21 GPa, and according to the buckling formula of thin-walled spherical shell Pc = 1.18×E×(h / R)², the target pressure threshold is 2.0 MPa.

[0056] In some implementations, nano-alumina is used as an inorganic brittle material, the average particle size of the fluid replenishment bladder is 25 μm, the thickness of the bladder shell is 800 nm, the Young's modulus of the bladder shell is adjusted to about 0.73 GPa, and according to the buckling formula of thin-walled spherical shell Pc = 1.18 × E × (h / R)², the target pressure threshold is 3.52 MPa.

[0057] In some implementations, nano-alumina is used as an inorganic brittle material, the average particle size of the fluid replenishment bladder is 16 μm, the thickness of the bladder shell is 300 nm, the Young's modulus of the bladder shell is adjusted to about 2 GPa, and according to the buckling formula of thin-walled spherical shell Pc = 1.18 × E × (h / R)², the target pressure threshold is 3.32 MPa.

[0058] Optionally, considering that the current density and operating temperature rise are high in the area around the battery cell terminals, the electrolyte is consumed faster and the interface drying problem is likely to occur, in this application, the electrolyte replenishment bag is set in the area around the battery cell terminals, which can replenish the electrolyte in time after the bag shell is broken, effectively improve the local liquid shortage situation and delay the degradation of battery cell performance.

[0059] Figure 2 This is an exemplary schematic diagram illustrating a method for preparing a rehydration bag as described in this application, used to prepare the rehydration bag as described above. Figure 2 As shown, the preparation method of this fluid replenishment bag includes the following steps: S201, the precursor used to form the inorganic brittle material is dissolved in an organic solvent to form a precursor solution.

[0060] The precursor solution formed includes precursors for forming inorganic brittle materials, thereby providing a raw material system for subsequent shell molding.

[0061] S202 uses a liquid substance as the core phase and a precursor solution as the basis to prepare a stable oil-in-liquid emulsion through a high-shear emulsification process. The liquid substance contains the same or partially the same components as the electrolyte.

[0062] Specifically, a liquid substance is dispersed in a precursor solution as the core phase to form a coarse dispersion; the coarse dispersion is then subjected to high-shear emulsification to form a stable oil-in-liquid emulsion.

[0063] In the emulsification process, the liquid substance is dispersed into tiny core droplets, which are then encapsulated by the precursor solution as an organic continuous phase to form emulsion droplets. Furthermore, the precursor is enriched at the interface of the emulsion droplets.

[0064] S203, an oil-in-liquid emulsion is subjected to interfacial gel encapsulation and heating sintering treatment to prepare a liquid replenishment bag.

[0065] Specifically, the process of interfacial gel encapsulation of oil-in-liquid emulsions includes: introducing water vapor or aqueous solution into the oil-in-liquid emulsion, and under the action of a catalyst, causing the precursor on the surface of the emulsion droplets to undergo interfacial hydrolysis and condensation reaction to achieve sol-gel conversion, thereby forming an inorganic gel shell in situ on the surface of the core phase.

[0066] Specifically, the heating sintering process includes: aging, washing, and drying the product after the interface gel is encapsulated, and then heating and sintering it under an inert atmosphere to dehydrate and densify the inorganic gel shell, transforming it into an inorganic brittle shell, thereby obtaining a liquid replenishment bladder with a complete structure and uniform strength.

[0067] Among them, the interface gel encapsulation treatment can form an inorganic gel shell in situ on the surface of the core phase, initially forming a shell prototype; while the heating sintering treatment can dehydrate and densify the inorganic gel shell, transforming it into the final inorganic brittle shell.

[0068] The replenishment bladder prepared by the above method has a target pressure threshold. When the local pressure inside the battery reaches the target pressure threshold, the bladder ruptures, accurately releasing a liquid substance that is the same as or partially the same as the electrolyte, and immediately immerses the surrounding liquid-deficient area to replenish the liquid-deficient area. This effectively alleviates interface drying, maintains ion transport, delays battery capacity decay and impedance growth, and extends battery life.

[0069] In some examples, the precursors used to form inorganic brittle materials may be aluminum alkoxides and / or silicates.

[0070] Optionally, if the precursor is an aluminum alkoxide, the inorganic brittle material of nano-alumina will be generated as the shell after the above process.

[0071] Optionally, if the precursor is a silicate ester, the above process will ultimately produce an inorganic brittle material of nano-silica as the shell.

[0072] Optionally, if the precursor is aluminum alkoxide and silicate, the final product after the above process is a composite inorganic brittle material composed of nano-alumina and nano-silica, which serves as the shell.

[0073] In some examples, if the above precursor is an aluminum alkoxide, aluminum isopropoxide may be used.

[0074] In some examples, if the precursor is a silicate ester, specifically tetraethyl orthosilicate may be used.

[0075] In this application, considering the mechanical model of a thin-walled spherical shell, the target pressure threshold (Pc) approximately satisfies: Pc = K × E × (h / R)² Where K is a fixed coefficient; E is the Young's modulus of the inorganic brittle material; h is the shell thickness; and R is the shell radius. Based on the above principle, this application can adjust the ratio of the shell thickness to the shell radius and the Young's modulus of the inorganic brittle material to achieve a target pressure threshold of 2.0 MPa to 4.0 MPa for the fluid replenishment bladder.

[0076] In some examples, the particle size of the replenishment bladder is controlled by adjusting the process parameters during high-shear emulsification (including but not limited to parameters such as the rotation speed of high-speed shear and emulsification time).

[0077] Optionally, the rotation speed during high-shear emulsification can be set to 3000~10000 rpm, with a preferred range of 4000~8000 rpm.

[0078] Optionally, the duration of high-shear emulsification treatment can be set to 3 to 20 minutes, with a preferred range of 5 to 15 minutes.

[0079] In some examples, during high-speed shear emulsification, the high-speed shearing speed was set to 4000–8000 rpm, and the emulsification time was controlled to be 5–15 min. By precisely controlling the shearing speed and emulsification time, the particle size of the prepared replenishment capsules can be stably controlled within the range of 8 μm to 25 μm.

[0080] In some examples, the thickness of the fluid replenishment bladder shell is controlled by adjusting at least one of the following parameters (by controlling the thickness of the inorganic gel shell layer, the thickness of the shell formed by the final temperature sintering is controlled): The concentration of the precursor in the precursor solution; The volume ratio of the core phase to the precursor solution; Rotation speed and / or duration of high-shear emulsification treatment.

[0081] The higher the concentration of the precursor in the precursor solution, the greater the thickness of the outer layer surrounding the core phase, and the greater the thickness of the final fluid replenishment capsule shell.

[0082] The smaller the volume ratio of the core phase to the precursor solution, the less core phase is added, and the greater the thickness of the final fluid replenishment capsule shell.

[0083] Optionally, assuming that the precursor is tetraethyl orthosilicate, the concentration of the precursor in the precursor solution can be set to 0.05 ~ 0.8 mol / L, preferably 0.2 ~ 0.5 mol / L.

[0084] Optionally, assuming that aluminum isopropoxide is used as the precursor, the concentration of the precursor in the precursor solution can be set to 0.3~1.5 mol / L, preferably 0.5~1 mol / L.

[0085] Optionally, the volume ratio of the core phase to the precursor solution can be set to 1:3 to 1:10, with a preferred range of 1:4 to 1:9.

[0086] Optionally, the rotation speed during high-shear emulsification can be set to 3000~10000 rpm, with a preferred range of 4000~8000 rpm.

[0087] Optionally, the duration of high-shear emulsification treatment can be set to 3 to 20 minutes, with a preferred range of 5 to 15 minutes.

[0088] In some examples, the final temperature range after the heating sintering process is 300℃-500℃ to adjust the crystallinity and density of the inorganic brittle shell layer, so that the Young's modulus of the final shell material is within the target range. The target range refers to the Young's modulus range required to achieve a target pressure threshold of 2.0 MPa to 4.0 MPa after the particle size and thickness of the replenishment bladder are determined, thus precisely setting the target pressure threshold of the replenishment bladder to 2.0 MPa to 4.0 MPa.

[0089] Optionally, if the sintering temperature is 300℃ and the precursor is aluminum alkoxide, the Young's modulus of the final nano-alumina material can be controlled between 0.3GPa and 2GPa by adjusting the sintering time.

[0090] Optionally, if the sintering temperature is 400℃ and the precursor is aluminum alkoxide, the Young's modulus of the final nano-alumina material can be controlled between 1GPa and 4GPa by adjusting the sintering time.

[0091] Optionally, if the sintering temperature is 500℃ and the precursor is aluminum alkoxide, the Young's modulus of the final nano-alumina material can be controlled between 2GPa and 8GPa by adjusting the sintering time.

[0092] Optionally, if the sintering temperature is 300℃ and the precursor is a silicate ester, the Young's modulus of the final nano-silica material can be controlled between 0.1GPa and 0.5GPa by adjusting the sintering time.

[0093] Optionally, if the sintering temperature is 400℃ and the precursor is a silicate ester, the Young's modulus of the final nano-silica material can be controlled between 0.3GPa and 1.2GPa by adjusting the sintering time.

[0094] Optionally, if the sintering temperature is 500℃ and the precursor is a silicate ester, the Young's modulus of the final nano-silica material can be controlled between 0.8GPa and 3GPa by adjusting the sintering time.

[0095] Considering that the fixed coefficient K is generally between 1.18 and 1.2 for nano-silica or nano-alumina, various examples will be given below using Pc = K × E × (h / R)².

[0096] In some implementations, if nano-alumina is planned to be used as an inorganic brittle material, the average particle size of the replenishment bladder is determined to be 8 μm and the thickness of the bladder shell is 150 nm. An inorganic gel shell layer is formed in situ on the surface of the core phase using the sol-gel method, and then sintered at 400℃ in an inert atmosphere for 2 h to adjust the Young's modulus of the bladder shell to about 1.21 GPa. According to the buckling formula of thin-walled spherical shell Pc = 1.18×E×(h / R)², the target pressure threshold is 2.0 MPa.

[0097] In some implementations, if nano-alumina is planned to be used as an inorganic brittle material, the average particle size of the replenishment bladder is determined to be 25 μm and the thickness of the bladder shell is 800 nm. An inorganic gel shell layer is formed in situ on the surface of the core phase using the sol-gel method, and then sintered at 300 °C in an inert atmosphere for 2 h to adjust the Young's modulus of the bladder shell to about 0.73 GPa. According to the buckling formula of thin-walled spherical shell Pc = 1.18 × E × (h / R)², the target pressure threshold is 3.52 MPa.

[0098] In some implementations, if nano-alumina is planned to be used as an inorganic brittle material, the average particle size of the replenishment bladder is determined to be 16 μm and the thickness of the bladder shell is 300 nm. An inorganic gel shell layer is formed in situ on the surface of the core phase using the sol-gel method, and then sintered at 500 °C in an inert atmosphere for 2 h to adjust the Young's modulus of the bladder shell to about 2 GPa. According to the buckling formula of thin-walled spherical shell Pc = 1.18 × E × (h / R)², the target pressure threshold is 3.32 MPa.

[0099] The aforementioned method for preparing the electrolyte replenishment bladder achieves an adjustable target pressure threshold by precisely controlling the bladder shell material (Al2O3 and / or SiO2), the particle size of the bladder shell, the bladder shell thickness, and the Young's modulus of the bladder shell material. This allows the bladder shell to rupture when the local pressure inside the battery reaches the target pressure threshold in the later stages of battery cycling, precisely releasing a liquid substance that is the same as or partially the same as the electrolyte. This replenishes the electrolyte-deficient area, delays battery capacity decay, extends cycle life, and improves battery performance in the later stages of its life cycle.

[0100] In some examples, the liquid material serving as the core phase also includes additives, such as one or more of fluoroethylene carbonate (FEC), vinylene carbonate (VC), and lithium difluorooxalate borate (LiDFOB). This allows the casing to rupture during the later stages of battery cycling when the local pressure inside the battery reaches the target pressure threshold. This releases not only the same or partially the same liquid material as the electrolyte but also the additives, replenishing the electrolyte and additives to the deficient areas. This, in turn, slows down battery capacity decay, extends cycle life, and improves battery performance in the later stages of its lifespan.

[0101] Figure 3 This is a cross-sectional schematic diagram of a composite diaphragm provided in an embodiment of this application. The composite diaphragm integrates or deploys the fluid replenishment bladder mentioned in the foregoing embodiments. For the specific structural features of the fluid replenishment bladder, please refer to the detailed explanation and description of the fluid replenishment bladder in the above embodiments; these details will not be repeated in the embodiments of this application.

[0102] In embodiments of this application, the composite diaphragm further includes: a diaphragm and an additional layer disposed on the diaphragm; the additional layer includes the fluid replenishment bladder described in any of the above embodiments.

[0103] The additional layer is disposed on at least one surface of the separator. Specifically, it can be disposed on the surface of the separator near the negative electrode to better replenish electrolyte in the low-lying areas of the battery. This is because during battery cycling, the negative electrode side experiences greater local expansion force and faster electrolyte consumption due to factors such as SEI film thickening, side reaction gas generation, and lithium deposition, making it more prone to interface drying and lithium plating. By placing the additional layer near the negative electrode side, the replenishment bladder can rupture directly in the most severely low-lying area when the pressure reaches a threshold, releasing liquid substances and achieving a more efficient and precise replenishment effect.

[0104] The separator can be a conventional porous polymer separator, preferably a polyolefin separator. Specifically, the polyolefin separator includes, but is not limited to, polyethylene (PE) single-layer separators, polypropylene (PP) single-layer separators, or PP / PE / PP three-layer composite separators. These materials possess good chemical stability, thermal shut-off characteristics, and mechanical strength, and their porous structure is beneficial for electrolyte wetting and lithium-ion transport.

[0105] In the embodiments of this application, an additional layer can be formed on one or both surfaces of the aforementioned polyolefin separator, thereby constructing a composite separator that combines ion conduction capability and liquid replenishment function. By introducing an additional layer containing a liquid replenishment bladder onto the surface of the polyolefin separator, in-situ replenishment of the battery separator can be achieved without changing the existing battery assembly process, thereby improving battery cycle life.

[0106] The additional layer is coated onto the diaphragm. The additional layer also includes an adhesive layer, within which the fluid replenishment bladder is located. Specifically, the additional layer comprises a porous mesh-like adhesive layer, within which the fluid replenishment bladder is dispersed.

[0107] It should be noted that the distribution of the replenishing bladders in the binder layer can be adjusted according to actual application requirements. When the internal mechanical stress distribution of the battery is relatively uniform, the replenishing bladders can be dispersed in a large number uniformly in the binder layer. That is, when the entire binder layer area remains non-uniform, the spatial distribution of local pressure during battery cycling can be determined through simulation or actual measurement, and then the replenishing bladders are arranged according to the determined spatial distribution. For example, if the pressure is high in the area corresponding to the negative electrode-separator interface, the replenishing bladders will be concentrated in the corresponding positions in the binder layer, while the replenishing bladders will be reduced or not arranged in low-stress areas. This non-uniform distribution can be achieved by controlling the local concentration of the replenishing bladders in the coating slurry, using a patterned coating process, or applying multiple coatings in different areas.

[0108] In the embodiments of this application, by adopting different strategies to determine the distribution of the replenishment bladder on the adhesive layer, it is possible to achieve on-demand replenishment of electrolyte and / or additives, which can improve replenishment efficiency, avoid the ineffective occupation of the replenishment bladder in unnecessary areas, and help maintain the balance of overall porosity and ionic conductivity of the diaphragm.

[0109] Specifically, the mass ratio of the fluid replenishment bladder to the binder is 20:80-30:70. That is, the fluid replenishment bladder can be mixed with the binder at a certain mass ratio, for example, 20 wt%, and dispersed in N-methylpyrrolidone (NMP) to form a uniform slurry. Then, the slurry is uniformly attached to at least one side of the diaphragm through conventional processes such as slot coating, spraying, or impregnation. Finally, after drying, a composite diaphragm is formed.

[0110] In this process, the adhesive layer self-assembles to form a continuous porous network skeleton, and the liquid filling bladder is wrapped in the network pores. This not only maintains its structural integrity, but also ensures that it can respond freely and rupture to release the liquid substance and / or additives in its containment cavity when subjected to local mechanical stress.

[0111] To balance replenishment efficiency and battery energy density, the distribution density of the replenishment sacs on the surface of the additional layer is 0.5 mg / cm²-5 mg / cm². When the distribution density of the replenishment sacs on the surface of the additional layer is too low, such as below 0.5 mg / cm², the number of replenishment sacs is insufficient, making it difficult to cover the main areas lacking liquid, resulting in limited replenishment effect. When the distribution density of the replenishment sacs on the surface of the additional layer is too high, such as exceeding 5 mg / cm², although the replenishment sac load can be increased, it will increase the proportion of inactive materials, reduce the volumetric / weight energy density of the battery, and may also lead to decreased flexibility due to excessive coating thickness, resulting in cracks during winding or assembly.

[0112] In a preferred embodiment of this application, in order to ensure effective replenishment capability while minimizing the negative impact on the overall battery performance, the distribution density of the liquid replenishment sacs on the surface of the additional layer can preferably be controlled within the range of 1 mg / cm² to 2 mg / cm². Furthermore, to achieve more efficient replenishment, this application can set the distribution density of the liquid replenishment sacs in the central region of the additional layer surface to be greater than or equal to the distribution density of the liquid replenishment sacs in its edge regions.

[0113] In the embodiments of this application, the adhesive layer may be one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), carboxymethyl cellulose (CMC), or styrene-butadiene rubber (SBR).

[0114] The aforementioned replenishment bladder's shell is made of an inorganic brittle material. Inorganic brittle materials possess high-precision triggering and excellent sealing properties, exhibiting extremely low permeability to organic electrolytes and lithium salt ions. This allows for long-term stable storage of the core's contents, ensuring "zero loss" of replenished substances before triggering. Furthermore, the inorganic brittle material is heat-resistant, adapting to the high-temperature operating environment of batteries. It is particularly suitable for the following scenarios: (1) Suitable for high-performance power batteries (main drive batteries for pure electric passenger vehicles): This type of application requires precise target pressure threshold of the replenishment bladder to ensure that replenishment is only performed when the electrode expansion pressure reaches the design value in the later stages of cycling. The clear on / off triggering characteristics (threshold error <10%) of the inorganic brittle material shell perfectly meet this requirement and are the optimal choice for scenarios with the highest requirements for the accuracy of replenishment timing.

[0115] (2) Applicable to high temperature fast charging batteries: The mechanical properties of the inorganic oxide shell are not sensitive to temperature. Under the high temperature fast charging conditions of 60-80°C, the target pressure threshold remains stable and will not shift due to temperature rise, ensuring the predictability of liquid replenishment behavior and batch consistency. It is especially suitable for high rate (3-5C) fast charging scenarios.

[0116] (3) Suitable for long-term storage / backup power / aerospace energy storage: The inorganic shell dense Si-O-Si or Al-O network has a near-zero permeability to organic electrolyte solvents and chromium salts, which can ensure that the core additives are zero-loss during the storage period of several years. It is the best choice for ultra-long storage applications such as long-term backup emergency power and satellite energy storage.

[0117] (4) Applicable to square aluminum-cased batteries and cylindrical batteries: These batteries have strong directional expansion of the electrode during cycling, and the mechanical stress distribution is concentrated and predictable. This is highly compatible with the precise pressure switching characteristics of the inorganic brittle shell, resulting in low risk in engineering applications. Al2O3 and SiO2 are commonly used materials for commercially available membrane ceramic coatings, and their electrochemical compatibility with the battery system has been fully verified.

[0118] This application provides a battery including a fluid replenishment bladder as described in the above embodiments, or a composite separator as described in the above embodiments.

[0119] The battery includes a positive electrode, a negative electrode, and a composite separator disposed between the positive and negative electrodes. For details regarding the specific structural features of the composite separator, please refer to the detailed explanation and description of the composite separator in the above embodiments; these details will not be repeated in the embodiments of this application.

[0120] In this embodiment, a composite separator (also referred to as a battery separator) is disposed between the positive and negative electrodes to isolate the two electrodes while allowing lithium ions to pass through. The composite separator can respond to local mechanical stress in the later stages of battery cycling, enabling in-situ replenishment of electrolyte and additives, thereby improving the cycle life and safety of the battery.

[0121] This application also provides a battery replenishment method (i.e., a method for using a replenishment bladder), applicable to the batteries mentioned in all the foregoing embodiments. Specifically, it includes the following methods: When the pressure outside the electrolyte reservoir of the battery exceeds the target pressure threshold, the reservoir ruptures and releases at least one of the electrolyte and additives encapsulated in the reservoir cavity, thereby replenishing the target area where the electrolyte reservoir is located in the battery.

[0122] The battery replenishment method proposed in this application involves rupturing the electrolyte and at least one of the electrolyte and additives encapsulated in the containment cavity of the battery when the pressure outside the electrolyte bladder exceeds a target pressure threshold. This precisely releases liquid substances and additives that are the same as or partially the same as the electrolyte, thereby replenishing the low-liquid area, delaying battery capacity decay, extending cycle life, and improving battery performance in the later stages of its life cycle.

[0123] It should be noted that in some implementations, Raman spectroscopy and ICP-MS can be used to detect whether there are residual Al2O3 or SiO2 nanosheet fragments in the battery, in order to determine whether the replenishment bladder has ruptured.

[0124] This application also provides a device, including the fluid replenishment bladder shown in the example of this application, or the composite diaphragm shown in the example of this application, or the battery shown in the example of this application.

[0125] The aforementioned equipment includes, but is not limited to, terminal devices such as vehicles, robots, spacecraft, ships, outdoor power supplies, and vacuum cleaners.

[0126] In the description of this application, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "upper", "lower", "front", "rear", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc., indicating the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, are only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application.

[0127] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0128] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.

[0129] Although embodiments of this application have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting this application. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of this application.

Claims

1. A fluid resuscitation bag, characterized in that, The device includes a shell made of an inorganic brittle material, the shell having a cavity containing a liquid substance that contains the same or partially the same components as an electrolyte, and the shell ruptures when the pressure outside the shell exceeds a target pressure threshold so that the liquid substance in the cavity flows out of the shell.

2. The fluid replacement bag according to claim 1, characterized in that, The target pressure threshold is 2.0 MPa to 4.0 MPa, the particle size of the capsule is 8 μm to 25 μm, and the thickness of the capsule is 150 nm to 800 nm.

3. The fluid resuscitation bag according to claim 1 or 2, characterized in that, The target pressure threshold is determined by the thickness of the shell, the radius of the shell, and the Young's modulus of the inorganic brittle material. The target pressure threshold is proportional to the square of the ratio of the thickness and the radius.

4. The fluid replenishment bladder according to any one of claims 1-3, wherein the fluid replenishment bladder is disposed in the periphery region of the electrode post of the battery cell.

5. The rehydration bag according to any one of claims 1-4, characterized in that, The inorganic brittle material is nano-silica and / or nano-alumina.

6. The rehydration bag according to any one of claims 1-5, characterized in that, The cavity is also encapsulated with an additive, which is one or more of fluoroethylene carbonate, vinylene carbonate, and lithium difluorooxalate borate.

7. A method for preparing a rehydration capsule as described in any one of claims 1-6, characterized in that, Includes the following steps: The precursor used to form the inorganic brittle material is dissolved in an organic solvent to form a precursor solution; Using a liquid substance as the core phase, and based on the precursor solution, a stable oil-in-liquid emulsion is prepared by a high-shear emulsification process. The liquid substance contains the same or partially the same components as the electrolyte. The oil-in-liquid emulsion was subjected to interfacial gel encapsulation and sintering treatment to prepare the replenishment bag.

8. The method according to claim 7, characterized in that, in: The precursor is an aluminum alkoxide and / or a silicate; and / or, The aluminum alkoxide is aluminum isopropoxide; and / or, The silicate ester used is tetraethyl orthosilicate.

9. The method according to claim 8 or 9, characterized in that, The method further includes: The particle size of the replenishment bladder is controlled by adjusting the rotation speed and duration of the high-shear emulsification process. Wherein, the rotational speed is 3000~10000 rpm, and / or the duration is 3~20 min.

10. The method according to any one of claims 7-9, characterized in that, The method further includes: The thickness of the infusion bag shell can be controlled by adjusting at least one of the following parameters: The concentration of the precursor in the precursor solution is 0.05 ~ 0.8 mol / L when tetraethyl orthosilicate is used as the precursor, and 0.3 ~ 1.5 mol / L when aluminum isopropoxide is used as the precursor. The volume ratio of the core phase to the precursor solution is 1:3 to 1:

10. The rotational speed and / or duration of the high-shear emulsification process.

11. A composite diaphragm, characterized in that, It includes a diaphragm and an additional layer disposed on the diaphragm, the additional layer including a fluid replenishment bladder as claimed in any one of claims 1 to 6.

12. The composite diaphragm according to claim 11, characterized in that, The additional layer also includes an adhesive layer, and the fluid filling bladder is located within the adhesive layer.

13. The composite diaphragm according to claim 11 or 12, characterized in that, The mass ratio of the fluid replenishment bladder to the adhesive is 20:80-30:

70.

14. A battery, characterized in that, It includes the fluid replenishment bladder according to any one of claims 1-6, or the composite diaphragm according to any one of claims 11-13.

15. A method for replenishing electrolyte in a battery, characterized in that, The battery as described in claim 14 is used to replenish the target area of ​​the battery by rupturing the shell of the replenishment bladder when the pressure outside the shell of the replenishment bladder is greater than a target pressure threshold, releasing at least one of the electrolyte and additives encapsulated in the containment cavity of the shell, thereby replenishing the target area of ​​the battery where the replenishment bladder is located.

16. A device, characterized in that, Includes the battery as described in claim 14, or the fluid replenishment bladder as described in any one of claims 1-6, or the composite separator as described in any one of claims 11-13.